Nutritional quality of dysphagia-oriented products sold on the Italian market - Ascrizzi, Giorgio Innocenzo; Martini, Daniela; Piazza, Laura (Frontiers in Nutrition, 2024)
Dysphagia is a condiGon characterized by swallowing difficulGes that affects an esGmated 8% of the populaGon. Management of dysphagia oWen requires the use of specially formulated food products that are easier to swallow, while sGll meeGng the nutriGonal needs of the paGent. Despite the growing market for dysphagia-oriented products, there is a compelling need for comprehensive evaluaGons of their nutriGonal quality to ensure that they adequately support the health and well-being of this vulnerable populaGon. The aims of this study were: (i) to invesGgate the nutriGonal composiGon of different dysphagia products currently sold in Italy, from several leading healthcare companies, by collecGng the nutriGonal informaGon on their packaging; (ii) to compare their energy, nutrient and salt content per 100 g and serving. A total of 70 items, available in the Italian online market were included in the analysis. The data showed a wide difference among the six categories of dysphagia-oriented products. Salt content was found to be very high, with medium (>0.3 g/100 g but <1 g/100 g) and high (≥1 g/100 g) content found in 17% and 51% of products, respecGvely. Overall, the results show high variability in nutriGonal composiGon among dysphagia-oriented products currently on the market. The high presence of salt in more than half of the products raises a criGcal issue, as it is not in accordance with WHO guidelines and especially with the clinical situaGon of the dysphagia paGent. This research seeks to provide valuable insights into the adequacy of these products in meeGng the dietary requirements of individuals with dysphagia, thereby guiding toward more informed and suitable food choices.